2012
DOI: 10.1002/jcop.21517
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Motherhood and Capital: Interaction Effects of Race/Ethnicity on Harsh Parenting

Abstract: This study used large, longitudinal data to examine the moderating effects of race and ethnicity of mothers on the associations between (a) adolescent motherhood, (b) human, social, and cultural capital factors, and (c) harsh parenting. The study sample included adolescent mothers who were 19 years old or younger (n = 379) and adult mothers 26 years old or older (n = 881). Of these, about 31% were White, 48% Black, and 21% Hispanic. The Parent to Child version of the Conflict Tactics Scales was used as a proxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…The results indicated that children's gender and age as well as mothers' age and education status did not show between-group differences in maternal rejection, but mothers' employment and economic statuses did. This is consistent with the results of prior studies that demonstrated environmental influences such as financial instability in the family, parental age, and ethnicity as the most important predictors of harsh parenting strategies (Galovan et al, 2013;Y. Y. Lee, 2013;McGroder, 2000).…”
Section: Moderating Role Of Culturesupporting
confidence: 92%
“…The results indicated that children's gender and age as well as mothers' age and education status did not show between-group differences in maternal rejection, but mothers' employment and economic statuses did. This is consistent with the results of prior studies that demonstrated environmental influences such as financial instability in the family, parental age, and ethnicity as the most important predictors of harsh parenting strategies (Galovan et al, 2013;Y. Y. Lee, 2013;McGroder, 2000).…”
Section: Moderating Role Of Culturesupporting
confidence: 92%
“…Adolescent mothers also appear to be at greater risk for psychological distress before teenage childbearing and over the life course (Mollborn and Morningstar 2009; Shaw et al 2006). In terms of parenting and child outcomes, some studies suggest that teenage mothers exhibit less optimal parenting practices relative to older mothers (Lee 2013; Lewin et al 2013) and that adolescent children of teenage mothers are more likely to have behavior and substance use problems (Harden et al 2007; Shaw et al 2006). There is also evidence that growing up in a single parent family, more generally, is a risk factor for adolescent drinking (Brown and Rinelli 2010; Oman et al 2007).…”
Section: The Current Studymentioning
confidence: 99%
“…Despite this within-group ethnoracial diversity, family research continues to treat individuals who identify as Black 1 as belonging to a racially homogenous group (Hill et al, 2005). This homogenous view of Black families is exacerbated by overreliance on between-race comparisons that conflate racial/ethnic differences with socioeconomic status (i.e., White middle-class vs. Black low-income) and then portray caregiving practices within low-income, Black families as harsh, disorganized, and harmful (Lee, 2013; McWayne et al, 2017).…”
mentioning
confidence: 99%